Kristologi : Memahami Gelar Yesus Kristus - Marlen Alakaman (TANGKOLEH PUTAI, 2019)
People know God through Jesus Christ. The figure of Jesus in the reality of his life in the world together with his disciples and also those around him who met in His ministry were doing. Christology is a picture of discourse in which wiil be discoussed about the litles of Jesus. In interpreting the title of Jesus, there are two approaches used, namely Christology from below, it is approaching Jesus as a real human being and Christology from above, namely approaching Jesus from God as God.